High Selectivity and Stability Structure of Layered Double Hydroxide-Biochar for Removal Cd(II) - Neza Rahayu Palapa; Patimah Mega Syah Bahar Nur Siregar; Alfan Wijaya; Tarmizi Taher; Aldes Lesbani (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Composite M2+/Al-BC (Ca/Al-BC, Cu/Al-BC, and Ni/Al-BC) have been successfully synthesized. Composite and pristine materials were used as adsorbents of cadmium(II) [Cd(II)] in an aqueous solution. Firstly the performance of composite and pristine materials was evaluated by reusability properties until five cycles adsorption process followed with a determination of isotherms and adsorption thermodynamic properties. The results show composite has ten-fold surface area properties than starting materials. The adsorption capacities of CaAl-BC, CuAl-BC, and NiAl-BC at a temperature of 333 K were 156.250 mg/g, 149.254 mg/g, and 208.333 mg/g, respectively. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).